Analyzing the Implementation of Kurikulum Merdeka: Insights from Chemistry Educators in Gunung Kidul Vocational Schools - Faizal Akhmad Adi Masbukhin; Inas Sausan (Postgraduate, University of Mataram, 2023)
The implementation of Kurikulum Merdeka, a crucial education initiative introduced by the Indonesian government to enhance national education quality, is particularly significant in Vocational Schools (Sekolah Menengah Kejuruan/SMK). These schools play a strategic role in preparing students with relevant skills for the workforce. Chemistry educators in vocational schools could develop alternative learning materials aligned with the latest curriculum standards through the implementation of Kurikulum Merdeka. This qualitative descriptive study employed a survey method, utilizing a specially designed questionnaire to measure the perspectives of chemistry educators regarding Kurikulum Merdeka. The survey involved 32 diverse chemistry teachers in SMKs across Gunung Kidul who had implemented Kurikulum Merdeka. Results indicate a strong commitment among educators to curriculum updates and alignment with student needs. While positive progress is noted in implementing a differentiated learning approach, attention is needed to provide additional programs for students struggling with understanding materials. Moreover, sustained efforts are required for effective community engagement and the development of a structured framework for data-based interventions. Overall, this study provides valuable insights into the challenges and opportunities of implementing Kurikulum Merdeka in vocational schools, offering recommendations for improvement.